Columbo murder in Malibu. ([United States s.n., 1990)
A popular romance novelist is murdered and her philandering boyfriend is the prime suspect.
VHS.
Peter Falk, Andrew Stevens, Brenda Vaccaro.
Keywords: Columbo, Lieutenant (Fictitious character).; Feature films -- United States; Detective and mystery films